Analisis Dampak Sosial Ekonomi dalam Pembangunan Bandara Yogyakarta International Airport (YIA) di Kabupaten Kulonprogo - Happy Susanto (Majalah Ilmiah Bijak, 2020)
The development of Yogyakarta International Airport (YIA) in Kulonprogo, Daerah Istimewa Yogyakarta (DIY), is the intention of the central government and regional governments to increase economic growth, develop regional infrastructure, and develop the social life of the community. The development of the YIA is also expected to provide great benefits for the development of tourism, so an air transportation infrastructure improvement is needed. The construction of this international airport has had socio-economic impacts on the lives of surrounding communities, both positive and negative impacts. The purpose of this study is to understand and describe how the socio-economic impact of YIA Airport development and how the strategies can be carried out by the government to overcome the impact of the development. This research uses descriptive method with a qualitative approach to explore the meaning of a phenomenon that occurs. Data collection techniques carried out by observation, direct interviews, documentation, and triangulation, so that data and information can be obtained that support the purpose of the study.